Positive electrode materials and their uses
The introduction of a rock salt phase coating layer on nickel-based secondary particles in lithium-ion batteries addresses the low lithium ion diffusion issue, improving charge/discharge efficiency and energy density.
Patent Information
- Application Number
- JP2024559224
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-06
- Filing Date
- 2023-03-27
- Publication Date
- 2025-04-16
AI Technical Summary
Nickel-based electrode active materials for lithium-ion batteries have low lithium ion diffusion coefficients, leading to poor charge/discharge efficiency and electrochemical performance.
A positive electrode material with a core-shell structure, where secondary particles formed by stacking primary particles are coated with a rock salt phase coating layer, enhancing lithium ion transfer and electrochemical stability.
The proposed positive electrode material improves lithium ion transfer rates, enhances rate performance, and maintains capacity retention, contributing to the development of high energy density secondary batteries.
Smart Images

Figure 2025511764000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This disclosure claims priority to Chinese Patent Application No. 202210353912.1, filed on April 6, 2022, and entitled “POSITIVE ELECTRODE MATERIAL AND USE THEREOF,” which is hereby incorporated by reference in its entirety.
[0002] The present disclosure relates to the technical field of secondary batteries, specifically to positive electrode materials and uses thereof. [Background technology]
[0003] Nickel-based electrode active materials are considered as promising positive electrode materials for lithium-ion batteries due to the advantages of high specific capacity, high energy density, environmental compatibility, and good safety. However, nickel-based electrode active materials have a low lithium ion diffusion coefficient, which leads to low charge-discharge efficiency of the material and poor electrochemical performance of the battery. Therefore, it is necessary to improve the structure of nickel-based electrode active materials to improve the lithium ion transport performance of nickel-based electrode active materials and improve the electrochemical performance of the battery. Summary of the Invention [Means for solving the problem]
[0004] In a first aspect, the present disclosure provides a positive electrode material. The positive electrode material includes secondary particles and a rock salt phase coating layer disposed on a surface of the secondary particles. The secondary particles are formed by stacking a plurality of primary particles. A ratio of a particle size of the secondary particles to an average particle size of the plurality of primary particles is 1.5 or more. The primary particles and the rock salt phase coating layer each include a nickel-based active material.
[0005] In some embodiments of the present disclosure, the nickel-based active material and the rock salt phase coating layer each have the chemical formula: Li 1-a A b (Ni m M 1-m )X x O2Z z[where -0.1 ≤ a ≤ 0.1, A contains one or more of Na, K, Be, Mg, Ca, and B, 0 ≤ b ≤ 0.1, M contains one or more of Mn, Co, and Al, 0 < m ≤ 1, X contains one or more of Zr, V, Ti, Cr, Fe, Co, Ni, Zn, Nb, Mo, Os, W, and Y, 0 ≤ x ≤ 0.1, Z contains one or more of F, Cl, Br, and I, and 0 ≤ z ≤ 0.1] contains the material.
[0006] In some embodiments of the present disclosure, the coverage rate of the rock salt phase coating layer on the surface of the secondary particles is in the range of 10% to 90%.
[0007] In some embodiments of the present disclosure, when the coverage rate is 20% or less, the ratio r of the particle size of the secondary particles to the average particle size of the plurality of primary particles satisfies 1.5 ≤ r ≤ 3.
[0008] When the coverage rate is greater than 20% and 50% or less, the ratio r of the particle size of the secondary particles to the average particle size of the plurality of primary particles satisfies 3 < r ≤ 10.
[0009] When the coverage rate is greater than 50% and 80% or less, the ratio r of the particle size of the secondary particles to the average particle size of the plurality of primary particles satisfies 10 < r ≤ 50.
[0010] When the coverage rate is greater than 80%, the ratio r of the particle size of the secondary particles to the average particle size of the plurality of primary particles satisfies r > 50.
[0011] In some embodiments of the present disclosure, the coverage rate of the rock salt phase coating layer on the surface of the secondary particles is in the range of 50% to 80%.
[0012] In some embodiments of the present disclosure, the particle size of the secondary particles is 15 μm or less.
[0013] In some embodiments of the present disclosure, the thickness of the rock salt phase coating layer is in the range of 1 nm to 20 nm.
[0014] In some embodiments of the present disclosure, the thickness of the rock salt phase coating layer ranges from 5 nm to 15 nm.
[0015] In some embodiments of the present disclosure, the nickel-based active material has a layered hexagonal close-packed structure and belongs to the space group R3m; in the X-ray diffraction pattern of the cathode material, the full width at half maximum of the diffraction peak of the (104) crystal plane of the cathode material is 0.1 to 0.2.
[0016] In some embodiments of the present disclosure, the full width at half maximum of the diffraction peak of the (104) crystal plane of the cathode material is 0.105 to 0.130.
[0017] In some embodiments of the present disclosure, the rock salt phase coating layer and the nickel-based active material each contain doped lithium nickel cobalt manganese oxide or undoped lithium nickel cobalt manganese oxide.
[0018] In some embodiments of the present disclosure, the undoped lithium nickel cobalt manganese oxide is Li(Ni m Co n Mn 1-m-n )O2 [where 0 < m < 1, 0 < n < 1, and 0 < m + n < 1].
[0019] In some embodiments of the present disclosure, the doping elements of the doped lithium nickel cobalt manganese oxide include one or more of Na, K, Be, Mg, Ca, B, Zr, V, Ti, Cr, Y, Fe, Co, Ni, Zn, Nb, Mo, Os, W, F, Cl, Br, and I.
[0020] In some embodiments of the present disclosure, the doped lithium nickel cobalt manganese oxide or the undoped lithium nickel cobalt manganese oxide is Li 1-a A b (Ni m Co n Mn 1-m-n )X x O2Z zwhere -0.1≦a≦0.1, A includes one or more of Na, K, Be, Mg, Ca, and B, and 0≦b≦0.1, X includes one or more of Zr, V, Ti, Cr, Fe, Co, Ni, Zn, Y, Nb, Mo, Os, and W, and 0≦x≦0.1, and Z includes one or more of F, Cl, Br, and I, and 0≦z≦0.1.
[0021] In a second aspect, the present disclosure provides a positive electrode sheet, the positive electrode sheet including a current collector and the positive electrode material according to the first aspect disposed on the current collector.
[0022] In a third aspect, the present disclosure provides a secondary battery comprising a positive electrode and a negative electrode, the positive electrode comprising the positive electrode sheet according to the second aspect.
[0023] In some embodiments of the present disclosure, the secondary battery further includes an electrolyte and a separator located between the positive electrode and the negative electrode.
[0024] In some embodiments of the present disclosure, the secondary battery further includes a solid or semi-solid electrolyte located between the positive electrode and the negative electrode.
[0025] In a fourth aspect, the present disclosure provides a vehicle, the vehicle including the secondary battery according to the third aspect. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a schematic diagram showing the structure of a cathode material provided in an embodiment of the present disclosure. [Diagram 2] 2(a) is a scanning electron microscope image characterizing the surface of the positive electrode material obtained in Example 4 of the present disclosure; FIG. 2(b) is an HR-TEM Fourier transform spectrum of a rock salt phase coating layer in the positive electrode material obtained in Example 4; and FIG. 2(c) is an HR-TEM Fourier transform spectrum of a core secondary particle in the positive electrode material obtained in Example 4. [Diagram 3]FIG. 3(a) is a transmission electron microscope image characterizing a cross-section of the positive electrode material obtained in Example 4 of the present disclosure; FIG. 3(b) is an HR-TEM Fourier transform spectrum of a rock salt phase coating layer in the positive electrode material obtained in Example 4; and FIG. 3(c) is an HR-TEM Fourier transform spectrum of a core secondary particle in the positive electrode material obtained in Example 4. [Figure 4] 1 is an XRD pattern of a positive electrode material obtained in Example 4 of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The technical solutions according to the embodiments of the present disclosure are described in detail below in combination with the accompanying drawings of the embodiments of the present disclosure. The described embodiments are obviously only a part, not all, of the embodiments of the present disclosure. Based on the embodiments of the present disclosure, all other embodiments obtained by those skilled in the art without creative efforts shall be within the protection scope of the present invention.
[0028] The present disclosure provides a positive electrode material that has a high lithium ion transfer rate, which, when applied to a battery, can improve the rate performance and capacity retention of the battery, contributing to the production of a secondary battery with a high energy density.
[0029] Nickel-based electrode active materials are considered promising cathode materials for lithium-ion batteries because of their high specific capacity. However, the lithium-ion diffusion coefficient of nickel-based electrode active materials is low, the charge and discharge efficiency of the materials is low, and the electrochemical performance of the battery is poor. In order to improve the lithium-ion migration performance of nickel-based electrode active materials and improve the electrochemical performance of the battery, the present disclosure provides a cathode material. FIG. 1 is a schematic diagram showing the structure of the cathode material provided in the embodiment of the present disclosure. In FIG. 1, the cathode material 100 includes secondary particles 10 and a rock salt phase coating layer 20 provided on the surface of the secondary particles 10, and the secondary particles 10 are formed by laminating a plurality of primary particles. In the embodiment of the present disclosure, the ratio of the particle size of the secondary particles to the average particle size of the primary particles is 1.5 or more. The primary particles and the rock salt phase coating layer each contain a nickel-based active material.
[0030] The cathode material of the present disclosure has a core-shell structure. In some embodiments, the core of the cathode material includes secondary particles, and the shell of the cathode material includes a rock salt phase coating layer. In some embodiments of the present disclosure, the nickel-based active material has the chemical formula Li 1-a A b (Ni m M 1-m )X x O2Z z [where -0.1 ≦ a ≦ 0.1, A includes one or more of Na, K, Be, Mg, Ca, and B, 0 ≦ b ≦ 0.1, M includes one or more of Mn, Co, and Al, 0 < m ≦ 1, X includes one or more of Zr, V, Ti, Cr, Fe, Co, Ni, Zn, Nb, Mo, Os, W, and Y, 0 ≦ x ≦ 0.1, Z includes one or more of F, Cl, Br, and I, and 0 ≦ z ≦ 0.1]. In the present disclosure, the secondary particles have a layered hexagonal close-packed structure and belong to the space group R3m; in the XRD pattern, crystal planes 003, 101, and 104 can be observed. In some embodiments of the present disclosure, the rock salt phase coating layer has the chemical formula Li 1-a A b (Ni m M 1-m )X x O2Z z[wherein, -0.1 ≦ a ≦ 0.1, A contains one or more of Na, K, Be, Mg, Ca, and B, 0 ≦ b ≦ 0.1, M contains one or more of Mn, Co, and Al, 0 < m ≦ 1, X contains one or more of Zr, V, Ti, Cr, Fe, Co, Ni, Zn, Nb, Mo, Os, W, and Y, 0 ≦ x ≦ 0.1, Z contains one or more of F, Cl, Br, and I, and 0 ≦ z ≦ 0.1]. In the present disclosure, the structure of the rock salt phase coating layer belongs to the space group Fm3m, and crystal planes 111 and 200 can be seen in the XRD pattern.
[0031] In the present disclosure, the structure of the secondary particles of the nickel-based active material expands the diffusion path of lithium ions, thereby effectively improving the movement speed of lithium ions in the material. The rock salt phase coating layer can improve the electrolyte retention ability of the positive electrode material, enable the electrolyte to continuously penetrate the positive electrode material, and realize regular diffusion of lithium ions. Furthermore, the rock salt phase coating layer can suppress the destruction of secondary particles and improve the structural stability of the positive electrode material. In particular, in the charge and discharge process of the battery, lithium ions continuously intercalate into and deintercalate from the secondary particles. The primary particles within the secondary particles continuously experience volume expansion and contraction, and the gaps between the particles are constantly changing. As a result, the electrolyte between the primary particles tends to generate bubbles. The presence of bubbles blocks the movement path of lithium ions in the electrolyte, making the movement path of lithium ions unstable, reducing the movement speed of lithium ions, and deteriorating the rate performance of the material. The rock salt phase coating layer has high structural strength, can prevent volume change of particles, reduce the generation of bubbles, and improve the stability of the movement of lithium ions in the electrolyte. Also, the rock salt phase coating layer has good electrolyte permeability. Due to capillary action, the electrolyte can penetrate into the secondary particles, thereby improving the contact area between the electrolyte and the primary particles. This is beneficial for expanding the movement path of lithium ions, improving the lithium ion movement performance of the Ni-Co-Mn ternary system positive electrode material, and improving the electrochemical performance of the battery.
[0032] In the positive electrode material of the present disclosure, the secondary particles of the nickel-based active material are formed by stacking a plurality of primary particles of the nickel-based active material. The structure of the secondary particles expands the solid-solid transport path of lithium ions in the nickel-based active material, and the secondary particles have a through-hole structure, which facilitates the penetration of the electrolyte, expands the lithium ion transport path, and improves the ion migration speed. The rock salt phase coating layer improves the electrolyte retention ability of the positive electrode material, allowing the electrolyte to continuously penetrate the secondary particles, which can improve the lithium ion migration performance of the Ni-Co-Mn ternary positive electrode material and improve the electrochemical performance of the battery.
[0033] In some embodiments of the present disclosure, the coverage of the rock salt phase coating layer on the surface of the secondary particles is in the range of 10% to 90%. The coverage refers to the ratio of the coverage area of the rock salt phase coating layer on the surface of the secondary particles to the surface area of the secondary particles. The coverage of the rock salt phase coating layer on the surface of the secondary particles may be specifically, but is not limited to, 10%, 30%, 50%, 60%, 70%, 80%, or 90%. By controlling the coverage of the rock salt phase coating layer, the coating layer can provide a favorable support for the secondary particles, so that the volume change of the secondary particles is suppressed and the entire material has good lithium ion migration performance. In some embodiments of the present disclosure, the coverage of the rock salt phase coating layer on the secondary particles is in the range of 50% to 80%.
[0034] In some embodiments of the present disclosure, the thickness of the rock salt phase coating layer is in the range of 1 nm to 20 nm. The thickness of the rock salt phase coating layer may be specifically 1 nm, 3 nm, 5 nm, 10 nm, 15 nm or 20 nm, but is not limited thereto. By controlling the thickness of the rock salt phase coating layer, the electrolyte retention ability of the positive electrode material is improved, and the electrolyte can sufficiently permeate the positive electrode. In some embodiments of the present disclosure, the thickness of the rock salt phase coating layer is in the range of 5 nm to 15 nm.
[0035] The inventors have found that the coating area of the rock salt phase coating layer is somewhat related to the structure of the secondary particles, and the lithium ion migration performance can be synergistically adjusted thereby. In some embodiments of the present disclosure, when the coating rate of the rock salt phase coating layer on the surface of the secondary particles is 20% or less, the ratio r of the particle size of the secondary particles to the average particle size of the primary particles is in the range of 1.5 to 3, that is, 1.5 ≤ r ≤ 3. When the coating rate of the rock salt phase coating layer on the surface of the secondary particles is greater than 20% and 50% or less, the ratio r of the particle size of the secondary particles to the average particle size of the primary particles is greater than 3 and 10 or less, that is, 3 < r ≤ 10. When the coating rate of the rock salt phase coating layer on the surface of the secondary particles is greater than 50% and 80% or less, the ratio r of the particle size of the secondary particles to the average particle size of the primary particles is greater than 10 and 50 or less, that is, 10 < r ≤ 50. When the coating rate of the rock salt phase coating layer on the surface of the secondary particles is greater than 80%, the ratio r of the particle size of the secondary particles to the average particle size of the primary particles is greater than 50, that is, r > 50. That is, for a single positive electrode material particle, when the coating rate of the rock salt phase coating layer is 20% or less, the particle size of the secondary particles is 1.5 to 3 times the average particle size of the primary particles. For example, when n primary particles are stacked to form secondary particles, if the average particle size of the n primary particles is x μm and the particle size of the secondary particles is y μm, when the coating rate of the rock salt phase coating layer is 20% or less, y / x = 1.5 to 3. The research of the present disclosure has found that when the particle size difference between the secondary particles and the primary particles is large, the lithium ion migration rate can be effectively improved. However, the volume change of the secondary particles is significant, and bubbles are likely to occur between the primary particles. The rock salt phase coating layer can effectively suppress the generation of bubbles and allow the electrolyte to come into sufficient contact with the primary particles, so that lithium ions can move regularly and have a high transport rate. However, if the coating rate is too high, it will affect the rate performance of the electrode material. Therefore, for a specific structure of the secondary particles, by controlling the coating rate of the rock salt phase coating layer, the material can have good lithium ion migration performance, that is, the material has a high lithium ion migration rate and lithium ions can move regularly, so the material has good cycle stability.
[0036] In some embodiments of the present disclosure, the average particle size of the secondary particles is 15 μm or less. The average particle size of the secondary particles may be, but is not limited to, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 10 μm, 11 μm, 13 μm, or 15 μm.
[0037] In some embodiments of the present disclosure, primary particles are densely stacked to form secondary particles. In the X-ray diffraction pattern of the positive electrode material, the full width at half maximum FWHM of the diffraction peak of the 104 crystal plane of the positive electrode material is in the range of 0.1 to 0.2. The full width at half maximum FWHM of the diffraction peak of the 104 crystal plane of the positive electrode material may specifically include, but is not limited to, 0.1, 0.105, 0.11, 0.12, 0.13, 0.15, or 0.2. When the full width at half maximum FWHM of the diffraction peak of the 104 crystal plane of the positive electrode material is in the range of 0.1 to 0.2, a secondary battery with high energy density can be manufactured. In some embodiments of the present disclosure, in the X-ray diffraction pattern of the positive electrode material, the full width at half maximum FWHM of the diffraction peak of the 104 crystal plane is in the range of 0.105 to 0.13.
[0038] In some embodiments of the present disclosure, when a=0, b=0, x=0, and z=0, the nickel-based active material has the formula Li(Ni m M 1-m In some embodiments of the present disclosure, the nickel-based active material includes a lithium site doping element, the lithium site doping element being Li(Ni x M 1-x )O2. The lithium site doping elements have the chemical formula Li 1-a A b (Ni m M 1-m )X x O2Z zA in the formula b>0, i.e., A in the formula b>0. The lithium site doping element includes one or more of Na, K, Be, Mg, Ca, and B. The lithium site doping element can improve the mobility of lithium ions in the rock salt phase coating layer and the crystal lattice of the nickel-based active material. In some embodiments of the present disclosure, the nickel-based active material contains a transition metal doping element. The transition metal doping element is represented by the formula Li 1-a A b (Ni m M 1-m )X x O2Z z in the formula x>0. The transition metal doping element includes one or more of Zr, V, Ti, Cr, Y, Fe, Co, Ni, Zn, Nb, Mo, Os, and W. The transition metal doping element can improve the stability of the positive electrode material in the electrolyte, inhibit the intermixing of lithium and nickel, and improve the conductivity of lithium ions in the solid phase. In some embodiments of the present disclosure, the nickel-based active material contains an oxygen site doping element. The oxygen site doping element is represented by the formula Li 1-a A b (Ni m M 1-m )X x O2Z z Z in the formula z>0. The oxygen site doping element is Li(Ni x M 1-x ) partially replaces the oxygen atoms in O2. The oxygen site doping elements include one or more of F, Cl, Br, and I. The oxygen site doping elements can improve the structural stability of the rock salt phase coating layer and the nickel-based active material.
[0039] In some embodiments of the present disclosure, the rock salt phase coating layer and the nickel-based active material each comprise a doped or undoped lithium nickel cobalt manganese oxide. The undoped lithium nickel cobalt manganese oxide is Li(Ni m Co n Mn 1-m-n) It has a chemical formula of O2 [where 0 < m < 1, 0 < n < 1, and 0 < m + n < 1]. In some embodiments of the present disclosure, the doping element of the doped lithium nickel cobalt manganese oxide includes one or more of Na, K, Be, Mg, Ca, B, Zr, V, Ti, Cr, Y, Fe, Co, Ni, Zn, Nb, Mo, Os, W, F, Cl, Br, and I. The doping element can improve the structural stability of the rock salt phase coating layer and the lithium ion migration rate of the lithium nickel cobalt manganese oxide. In some embodiments of the present disclosure, the doped or undoped lithium nickel cobalt manganese oxide is Li 1-a A b (Ni m Co n Mn 1-m-n )X x O2Z z [where -0.1 ≤ a ≤ 0.1, A includes one or more of Na, K, Be, Mg, Ca, and B, 0 ≤ b ≤ 0.1, X includes one or more of Zr, V, Ti, Cr, Fe, Co, Ni, Zn, Y, Nb, Mo, Os, and W, 0 ≤ x ≤ 0.1, Z includes one or more of F, Cl, Br, and I, and 0 ≤ z ≤ 0.1].
[0040] The cathode material provided by the present disclosure effectively expands the migration path of lithium ions and improves the lithium ion migration rate due to the structure of the secondary particles and the rock salt phase coating layer. The cathode material having such a structure can reduce the impedance of the battery and achieve high-rate charge and discharge. When this cathode material is applied to a secondary battery, it is possible to improve the capacity and cycle performance of the secondary battery, contributing to the long-term use of the battery.
[0041] The present disclosure further provides a method for manufacturing the aforementioned cathode material. This method includes the following steps.
[0042] The nickel-cobalt-manganese hydroxide is mixed with a lithium source and sintered in an oxygen-containing atmosphere to obtain a positive electrode material, the oxygen content of which is in the range of 18% to 100%.
[0043] In some embodiments of the present disclosure, the method for producing nickel-cobalt-manganese hydroxide includes the following steps: A nickel source, a cobalt source, and a manganese source are dispersed in an alkaline solution to obtain nickel-cobalt-manganese hydroxide. The pH value of the alkaline solution ranges from 9 to 14. The alkaline solution includes one or more of an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, and an aqueous ammonia solution. The nickel source includes one or more of nickel nitrate, nickel sulfate, and nickel chloride. The cobalt source includes one or more of cobalt nitrate, cobalt sulfate, and cobalt chloride. The manganese source includes one or more of manganese nitrate, manganese sulfate, and manganese chloride. In some embodiments of the present disclosure, the method for producing nickel-cobalt-manganese hydroxide includes the following steps: A nickel source, a cobalt source, and a manganese source are dispersed in an alkaline solution in a molar ratio of (5-10):(0.5-1.5):(0.5-1.5), and stirred at 25°C to 45°C and 5 rpm to 100 rpm for 360 minutes to 1,080 minutes.
[0044] In some embodiments of the present disclosure, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium oxalate, and lithium acetate. In some embodiments of the present disclosure, the nickel-cobalt-manganese hydroxide and the lithium source are mixed in a molar ratio of 1:(0.9-1.2), and then a doping element is added to the mixture, where the doping element includes one or more of a lithium site doping element, a transition metal doping element, and an oxygen site doping element. In the present disclosure, the oxygen content in the oxygen-containing atmosphere affects the structure of the rock salt phase coating layer. By controlling the oxygen content in the oxygen-containing atmosphere, a rock salt phase coating layer having a stable structure can be formed, the adhesion strength of the rock salt phase coating layer to the secondary particles is improved, and the positive electrode material has good and stable electrolyte retention ability. In some embodiments of the present disclosure, the oxygen content in the oxygen-containing atmosphere is in the range of 19% by mass to 95% by mass. The oxygen content in the oxygen-containing atmosphere may be specifically, but is not limited to, 18 mass%, 20 mass%, 25 mass%, 30 mass%, 50 mass%, 60 mass%, 70 mass%, 80 mass%, 90 mass%, or 100 mass%.
[0045] In some embodiments of the present disclosure, the sintering temperature is in the range of 200°C to 980°C. The sintering temperature may be specifically, but is not limited to, 200°C, 300°C, 500°C, 600°C, 700°C, 750°C, 800°C, 850°C, 900°C, or 980°C. In some embodiments of the present disclosure, the sintering time is in the range of 8 hours to 32 hours. The sintering time may be specifically, but is not limited to, 8 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, or 32 hours. In some embodiments of the present disclosure, the firing temperature is in the range of 700°C to 1000°C, and the firing time is in the range of 12 hours to 36 hours. By controlling the firing time and temperature, a densely stacked secondary particle structure and a rock salt phase coating layer stably coated on the surface of the secondary particles can be formed. In some embodiments of the present disclosure, the sintering apparatus may be any one of a rotary furnace, a converter, a box furnace, a tube furnace, a roller kiln, a pusher kiln, or a fluidized bed.
[0046] In some embodiments of the present disclosure, nickel-cobalt-manganese hydroxide and a lithium source are sintered by gradient heating. The gradient heating is as follows: nickel-cobalt-manganese hydroxide and a lithium source are heated to 720°C at a heating rate of 10°C / min or less, held at this temperature for 1-9 hours, then heated to 1000°C at a heating rate of 15°C / min or less, and held at this temperature for 8-25 hours to obtain a positive electrode material. In some embodiments of the present disclosure, the gradient heating is as follows: nickel-cobalt-manganese hydroxide and a lithium source are heated to 500°C at a heating rate of 10°C / min or less, held at this temperature for 2-9 hours, then heated to 850°C at a heating rate of 13.3°C / min or less, and held at this temperature for 8-25 hours to obtain a positive electrode material.
[0047] The present disclosure further provides a positive electrode sheet. The positive electrode sheet includes a current collector and a positive electrode material layer disposed on the current collector. The positive electrode material layer includes a positive electrode material according to the present disclosure. In the present disclosure, the positive electrode material layer can be manufactured by mixing a positive electrode material, a conductive agent, a binder, and a solvent into a positive electrode slurry, and coating and drying the positive electrode slurry to obtain a positive electrode material layer. In the manufacture of the positive electrode slurry, the binder is first mixed with a solvent and stirred thoroughly, the conductive agent is added and stirred, and then the positive electrode material is added and stirred, and sieved to obtain a positive electrode slurry. The conductive agent, the binder, and the solvent are conventional choices in the battery field. For example, the binder may be one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyalkene, sodium carboxymethylcellulose (CMC), and sodium alginate. The conductive agent may be one or more selected from carbon nanotubes, carbon black, and graphene.
[0048] The present disclosure further provides a secondary battery. The secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator located between the positive electrode and the negative electrode. Alternatively, the secondary battery includes a positive electrode, a negative electrode, and a solid electrolyte or semi-solid electrolyte located between the positive electrode and the negative electrode. The positive electrode includes the positive electrode sheet provided in the present disclosure.
[0049] In the present disclosure, the negative electrode of the secondary battery may be any negative electrode known in the art. In the embodiment of the present disclosure, the negative electrode may include one or more of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, and the like. The silicon-based negative electrode may include a silicon-containing material such as silicon, silicon carbide, silicon oxide, or a metal silicide, or a mixture of the silicon-containing material and a non-silicon-containing material such as graphite. The tin-based negative electrode may include a tin-containing material such as tin, tin carbide, tin oxide, or a metal tin compound, or a mixture of the tin-containing material and a non-tin-containing material such as graphite. The lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy. In some embodiments of the present disclosure, the negative electrode current collector is a copper foil. The negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, soft carbon, lithium titanate, iron oxide, lithium titanium phosphate, titania, silicon, silicon monoxide, tin and its oxides, and antimony and its oxides. The binder includes one or more of polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR). The conductive agent includes one or more of acetylene black, Ketjen carbon black, Super-P, carbon nanotubes, carbon nanofibers, activated carbon, and graphene. In the present disclosure, the method of manufacturing the negative electrode may be any method known in the art.
[0050] In the present disclosure, the separator of the secondary battery may be any separator known to those skilled in the art. For example, the separator may be one or more of a microporous polyolefin membrane, polyethylene terephthalate, polyethylene felt, glass fiber felt, or microfiberglass paper.
[0051] In the present disclosure, the electrolyte of the secondary battery includes a solution of an electrolyte lithium salt in a non-aqueous solvent. In an embodiment of the present disclosure, the electrolyte lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorosilicate (Li2SiF6), lithium tetraphenylborate (LiB(C6H5)4), lithium chloride (LiCl), lithium bromide (LiBr), lithium chloroaluminate (LiAlCl4), lithium fluoroalkylsulfonate (LiC(SO2CF3)3)LiCH3SO3, LiN(SO2CF3)2, and LiN(SO2C2F5)2. In some embodiments of the present disclosure, the non-aqueous solvent includes one or more of a chain acid ester and a cyclic acid ester. In some embodiments of the present disclosure, the linear acid ester comprises one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), methyl propyl carbonate (MPC), and dipropyl carbonate (DPC). In some embodiments of the present disclosure, the linear acid ester comprises a linear organic ester containing fluorine, sulfur, or an unsaturated bond. In some embodiments of the present disclosure, the cyclic acid ester comprises one or more of ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), γ-butyrolactone (γ-BL), and sulfolactone. In some embodiments of the present disclosure, the cyclic acid ester comprises a cyclic organic ester containing fluorine, sulfur, or an unsaturated bond. In some embodiments of the present disclosure, the non-aqueous solvent comprises one or more of a linear ether and a cyclic ether solution. In some embodiments of the present disclosure, the cyclic ether comprises one or more of tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), 1,3-dioxolane (DOL), and 4-methyl-1,3-dioxolane (4-MeDOL). In some embodiments of the present disclosure, the cyclic ether comprises a cyclic organic ether containing fluorine, sulfur, or an unsaturated bond.In some embodiments of the present disclosure, the chain ether comprises one or more of dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), 1,2-dimethoxypropane (DMP), and diethylene glycol dimethyl ether (DG). In some embodiments of the present disclosure, the chain ether comprises a chain organic ether containing fluorine, sulfur, or an unsaturated bond. In some embodiments of the present disclosure, the concentration of the electrolyte lithium salt in the electrolyte solution is 0.1 mol / L to 15 mol / L. In some embodiments of the present disclosure, the concentration of the electrolyte lithium salt is 1 mol / L to 10 mol / L.
[0052] In embodiments of the present disclosure, the secondary battery can be manufactured by a lamination process or a winding process. In some embodiments of the present disclosure, the battery is manufactured by a lamination process.
[0053] The present disclosure further provides a vehicle, the vehicle including the secondary battery provided in the present disclosure, the vehicle being powered by the secondary battery.
[0054] The technical solutions of the present disclosure are further described in some embodiments.
[0055] Example 1 The positive electrode material was prepared by a process including the following steps.
[0056] Nickel nitrate, cobalt nitrate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 11) in a molar ratio of 6:2:2, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and yttrium oxide, heated to 500°C at a heating rate of 10°C / min in an oxygen-containing atmosphere with an oxygen content of 22 mass%, held at this temperature for 4 hours, then heated to 850°C at a heating rate of 13.3°C / min, held at this temperature for 16 hours to be sintered to obtain a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are LiNi 0.60 Co0.20 Mn 0.20 Y 0.02 It has the chemical formula O2.
[0057] The prepared positive electrode material, conductive agent and binder were dispersed in N-methylpyrrolidone in a mass ratio of 95:3:2 to obtain a positive electrode slurry. The conductive agent was conductive carbon black and the binder was PVDF. The positive electrode slurry was coated on the surface of an aluminum foil with a thickness of 20 um, dried and rolled to obtain a compact with a pressed density of 3.4 g / cm. 3 A positive electrode having a positive electrode active material layer of 1.0 g / cm was obtained. Graphite, carboxymethyl cellulose, and conductive carbon black were dispersed in N-methylpyrrolidone in a ratio of 95:3:2 to obtain a negative electrode slurry. The negative electrode slurry was coated on the surface of a copper foil, dried, and rolled to obtain a negative electrode slurry having a pressed density of 1.4 g / cm. 3 A negative electrode having a negative electrode active material layer of 1000 μm was obtained. The prepared positive electrode, the prepared negative electrode, and the microporous polyolefin membrane were wound to prepare a battery core. After packaging, an electrolyte solution containing 1 mol / L lithium hexafluorophosphate (the solvent was 1:1 EC:EMC) was injected to obtain a battery. The battery of Example 1 was named S1.
[0058] Example 2 In Example 2, the positive electrode material was manufactured via a process including the following steps.
[0059] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 10) in a molar ratio of 5:2:3, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and heated to 550°C at a heating rate of 10°C / min in an oxygen-containing atmosphere with an oxygen content of 21 mass%, held at this temperature for 4 hours, then heated to 900°C at a heating rate of 13.3°C / min, held at this temperature for 14 hours to sinter, thereby obtaining a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are LiNi 0.50 Co 0.20 Mn0.30 It has the chemical formula O2.
[0060] A secondary battery was produced in the same manner as in Example 1. The battery of Example 2 was named S2.
[0061] Example 3 In Example 3, the positive electrode material was produced via a process including the following steps.
[0062] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 12) in a molar ratio of 8:1:1, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and yttrium oxide, heated to 480°C at a heating rate of 10°C / min in an oxygen-containing atmosphere with an oxygen content of 35 mass%, held at this temperature for 3 hours, then heated to 700°C at a heating rate of 13.3°C / min, held at this temperature for 22 hours, and sintered to obtain a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are LiNi 0.8 Co 0.1 Mn 0.1 Y 0.02 It has the chemical formula O2.
[0063] A secondary battery was produced in the same manner as in Example 1. The battery of Example 3 was named S3.
[0064] Example 4 In Example 4, a positive electrode material was prepared via a process including the following steps.
[0065] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 11) in a molar ratio of 6:2:2, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide, heated to 700°C at a heating rate of 10°C / min in an oxygen-containing atmosphere with an oxygen content of 30 mass%, held at this temperature for 6 hours, then heated to 850°C at a heating rate of 13.3°C / min, held at this temperature for 13 hours, and sintered to obtain a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are LiNi 0.60 Co 0.20 Mn 0.20 It has the chemical formula O2.
[0066] A secondary battery was produced in the same manner as in Example 1. The battery of Example 4 was named S4.
[0067] Example 5 In Example 5, a positive electrode material was prepared via a process including the following steps.
[0068] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 12) in a molar ratio of 8:1:1, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and sodium chloride, heated to 550°C at a heating rate of 10.2°C / min in an oxygen-containing atmosphere with an oxygen content of 50 mass%, held at this temperature for 6 hours, then heated to 850°C at a heating rate of 13.8°C / min, held at this temperature for 14 hours, and sintered to obtain a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are Li 0.99 Na 0.01 Ni 0.8 Co 0.1 Mn 0.1 O2Cl 0.1 It has the chemical formula:
[0069] A secondary battery was produced in the same manner as in Example 1. The battery of Example 5 was named S5.
[0070] Example 6 In Example 6, a positive electrode material was prepared via a process including the following steps.
[0071] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 12) in a molar ratio of 8:1:1, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and elemental iodine, heated to 650°C at a heating rate of 11°C / min in an oxygen-containing atmosphere with an oxygen content of 60 mass%, held at this temperature for 3 hours, then heated to 930°C at a heating rate of 13.8°C / min, held at this temperature for 15 hours to sinter, thereby obtaining a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are LiNi 0.8 Co 0.1 Mn 0.1 O2I 0.1 It has the chemical formula:
[0072] A secondary battery was fabricated in the same manner as described in Example 1. The battery of Example 6 was named S6.
[0073] Example 7 In Example 7, a positive electrode material was prepared via a process including the following steps.
[0074] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 12) in a molar ratio of 8:1:1, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and nano-boron oxide, heated to 700°C at a heating rate of 13.3°C / min in an oxygen-containing atmosphere with an oxygen content of 90 mass%, held at this temperature for 6 hours, and then heated to 880°C at a heating rate of 13.3°C / min and held at this temperature for 19 hours to sinter, thereby obtaining a positive electrode material. The positive electrode material includes a core secondary particle and a rock salt phase coating layer. The core secondary particle and the rock salt phase coating layer are LiB 0.02 Ni 0.8 Co 0.1 Mn 0.1 It has the chemical formula O2.
[0075] A secondary battery was produced in the same manner as in Example 1. The battery of Example 7 was named S7.
[0076] Example 8 In Example 8, a positive electrode material was prepared via a process including the following steps.
[0077] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 12) in a molar ratio of 8:1:1, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and lithium fluoride, heated to 550°C at a heating rate of 10.3°C / min in an oxygen-containing atmosphere with an oxygen content of 90 mass%, held at this temperature for 4 hours, then heated to 960°C at a heating rate of 13.3°C / min, held at this temperature for 15 hours to sinter, and obtained a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are LiNi 0.80 Co 0.10 Mn 0.10 O2F 0.05 It has the chemical formula:
[0078] A secondary battery was produced in the same manner as in Example 1. The battery of Example 8 was named S8.
[0079] Example 9 In Example 9, a positive electrode material was prepared via a process including the following steps.
[0080] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 12) in a molar ratio of 8:1:1, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and sodium fluoride, heated to 440°C at a heating rate of 11.2°C / min in an oxygen-containing atmosphere with an oxygen content of 90 mass%, held at this temperature for 8 hours, then heated to 860°C at a heating rate of 13.3°C / min, held at this temperature for 20 hours, and sintered to obtain a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are Li 0.99 Na 0.01 Ni 0.8 Co 0.1 Mn 0.1 O2F 0.1 It has the chemical formula:
[0081] A secondary battery was produced in the same manner as in Example 1. The battery of Example 9 was named S9.
[0082] Example 10 In Example 10, a positive electrode material was prepared by a process including the following steps.
[0083] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 10) in a molar ratio of 4:3:3, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and heated to 580°C at a heating rate of 10.8°C / min in an oxygen-containing atmosphere with an oxygen content of 19 mass%, held at this temperature for 2 hours, then heated to 990°C at a heating rate of 13.3°C / min, held at this temperature for 17 hours, and sintered to obtain a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are LiNi 0.40 Co 0.30 Mn 0.30 It has the chemical formula O2.
[0084] A secondary battery was produced in the same manner as in Example 1. The battery of Example 10 was named S10.
[0085] Example 11 In Example 11, a positive electrode material was prepared by a process including the following steps.
[0086] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 10) in a molar ratio of 1:1:1, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide, beryllium fluoride, and lithium fluoride, heated to 550°C at a heating rate of 10°C / min in an oxygen-containing atmosphere with an oxygen content of 19 mass%, held at this temperature for 4 hours, then heated to 980°C at a heating rate of 14.1°C / min, held at this temperature for 16 hours, and sintered to obtain a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are Li 0.99 Be 0.01 Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O2F 0.05 It has the chemical formula:
[0087] The secondary battery was fabricated as described in Example 1. The battery of Example 11 was designated as S11.
[0088] Example 12 In Example 12, a positive electrode material was prepared by a process including the following steps.
[0089] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 10) in a molar ratio of 8:1:1, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and yttrium fluoride, heated to 550°C at a heating rate of 10°C / min in an oxygen-containing atmosphere with an oxygen content of 85 mass%, held at this temperature for 8 hours, then heated to 800°C at a heating rate of 13.3°C / min, held at this temperature for 20 hours, and sintered to obtain a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are Li 1.01 Ni 0.8 Co 0.1 Mn 0.1 Y 0.01 O2F 0.05 It has the chemical formula:
[0090] A secondary battery was produced in the same manner as in Example 1. The battery of Example 12 was named S12.
[0091] Comparative Example 1 In Comparative Example 1, a positive electrode material was manufactured through a process including the following steps.
[0092] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 10) in a molar ratio of 8:1:1, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and lithium fluoride, heated to 550°C at a heating rate of 10°C / min in an oxygen-containing atmosphere with an oxygen content of 5% by mass, held at this temperature for 8 hours, and then heated to 950°C at a heating rate of 13.3°C / min and held at this temperature for 18 hours to obtain a positive electrode material. The positive electrode material includes a nickel-based active material and does not have a rock salt phase coating layer on the surface, and the nickel-based active material is LiNi 0.8 Co 0.1 Mn 0.1 O2F 0.1 It has the chemical formula:
[0093] A secondary battery was produced in the same manner as in Example 1. The battery of Comparative Example 1 was named D1.
[0094] Comparative Example 2 In Comparative Example 2, a positive electrode material was produced by a process including the following steps.
[0095] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to an aqueous sodium hydroxide solution (pH 10) in a molar ratio of 8:1:1, stirred at 50 rpm at 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide and sodium fluoride, heated to 550°C at a heating rate of 10°C / min in an oxygen-containing atmosphere with an oxygen content of 10 mass%, held at this temperature for 4 hours, then heated to 900°C at a heating rate of 13.3°C / min, held at this temperature for 14 hours to sinter, thereby obtaining a positive electrode material. The positive electrode material includes a nickel-based active material and does not have a rock salt phase coating layer on the surface, and the nickel-based active material is Li 0.99 Na 0.01 Ni 0.8 Co 0.1 Mn 0.1 O2F 0.1 It has the chemical formula:
[0096] A secondary battery was produced in the same manner as in Example 1. The battery of Comparative Example 2 was named D2.
[0097] Comparative Example 3 In Comparative Example 3, a positive electrode material was produced through a process including the following steps.
[0098] Nickel sulfate, cobalt sulfate, and manganese sulfate were added to a sodium hydroxide aqueous solution (pH 10) in a molar ratio of 8:1:1, stirred at 50 rpm and 30°C, and then filtered to obtain nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese hydroxide was mixed with lithium hydroxide, zirconia, and sodium carbonate, and sintered in an oxygen-containing atmosphere with an oxygen content of 70 mass% at a sintering temperature of 840°C for a sintering time of 22 hours to obtain a positive electrode material. The positive electrode material includes core secondary particles and a rock salt phase coating layer. The core secondary particles and the rock salt phase coating layer are composed of Li 0.99 Na 0.01 Ni 0.8 Co 0.1 Mn 0.1 Zr 0.02 It has the chemical formula O2.
[0099] A secondary battery was produced in the same manner as in Example 1. The battery of Comparative Example 3 was named D3.
[0100] (Example of effect) To verify the performance of the positive electrode materials and batteries prepared in this disclosure, the present disclosure also provides examples.
[0101] FIG. 2 is a scanning electron microscope image characterizing the cathode material obtained in Example 4 of the present disclosure, in which FIG. 2(a) characterizes the morphology of the cathode material obtained in Example 4, FIG. 2(b) is an HR-TEM Fourier transform spectrum of the rock salt phase coating layer in the cathode material obtained in Example 4, and FIG. 2(c) is an HR-TEM Fourier transform spectrum of the core secondary particles in the cathode material obtained in Example 4. FIG. 2 can reflect the surface morphology information of the cathode material. From FIG. 2, it can be seen that in the cathode material of Example 4, the coverage rate of the rock salt phase coating layer is about 37%, the average particle size of the primary particles is 1.89 μm, the particle size of the secondary particles is 8.12 μm, and the ratio of the secondary particles to the diameter of the primary particles is 4.3. As can be seen from the crystal plane analysis, the rock salt phase coating layer belongs to the space group Fm3m, and the secondary particles belong to the space group R3m. FIG. 3 is a transmission electron microscope image characterizing the cross section of the cathode material obtained in Example 4 of the present disclosure, FIG. 3(a) characterizes the cross section of the cathode material obtained in Example 4, FIG. 3(b) is the HR-TEM Fourier transform spectrum of the rock salt phase coating layer in the cathode material obtained in Example 4, and FIG. 3(c) is the HR-TEM Fourier transform spectrum of the core secondary particle in the cathode material obtained in Example 4. From FIG. 3, it can be seen that the thickness of the rock salt phase coating layer is 15 nm in the cathode material of Example 4. The cathode materials of each Example and Comparative Example were characterized by the same method. The corresponding characterization results are shown in Table 1.
[0102] [Table 1]
[0103] The positive electrode material of Example 4 was characterized by X-ray diffraction, and the diffraction pattern was analyzed. FIG. 4 is the XRD pattern of the positive electrode material obtained in Example 4 of the present disclosure. As can be seen, the positive electrode material of Example 4 has a high crystallinity, the stability of the material is good, and the full width at half maximum FWHM of the diffraction peak of the (104) crystal plane of the positive electrode material is 0.117. The positive electrode materials of each example and comparative example were characterized by the same method. The corresponding characterization results are shown in Table 2.
[0104] [Table 2]
[0105] The batteries of each Example and Comparative Example were tested for charge-discharge cycling. Discharge rate test conditions: The batteries at 100% SOC were discharged to 2.5V at 5C and 25°C. The ratio of the discharge capacity to the nominal capacity was recorded to obtain the discharge rate of the battery. Capacity retention test conditions: After the batteries were charged and discharged 2000 times at 100% depth of discharge (DOD) and 1C, the capacity retention of the battery was calculated. The test results are shown in Table 3.
[0106] [Table 3]
[0107] In Table 3, the coverage of the rock salt phase coating layer of the positive electrode materials of Examples 1 and 2 is less than 20%. In the positive electrode material of Example 1, the ratio of the secondary particles to the particle size of the primary particles is appropriate, which facilitates the diffusion of lithium ions; the rock salt phase coating layer and the secondary particles are well matched, so the positive electrode material has good structural stability, and the battery has good cycle performance and rate performance. The coverage of the rock salt phase coating layer of the positive electrode materials of Examples 3 to 8 is in the range of 20% to 50%. In the positive electrode material of Example 3, the ratio of the secondary particles to the particle size of the primary particles is relatively small, and the coating layer is too thick, so the lithium ion migration performance is reduced, and the rate performance and cycle performance of the battery are poor. In the positive electrode material of Example 5, the structure of the coating layer and the secondary particles are well matched, and the resulting battery has not only a high discharge rate but also good cycle performance. In the positive electrode material of Example 8, the thickness of the coating layer is large, which reduces the rate performance of the material.
[0108] The coverage of the rock salt phase coating layer of the positive electrode material in Examples 9 and 10 is in the range of 50% to 80%. In the positive electrode material in Example 10, the particle size ratio of the secondary particles to the primary particles is appropriate, which facilitates the diffusion of lithium ions; the structure of the coating layer and the secondary particles is well matched, so the positive electrode material has good structural stability, and the battery has good cycle performance and rate performance. The coverage of the rock salt phase coating layer of the positive electrode material in Examples 11 and 12 is greater than 80%. In the positive electrode material in Example 12, the particle size ratio of the secondary particles to the primary particles is appropriate, which facilitates the diffusion of lithium ions; the structure of the coating layer and the secondary particles is well matched, so the positive electrode material has good structural stability, and the battery has good cycle performance and rate performance.
[0109] The positive electrode material of Comparative Example 1 does not have a coating layer and is formed of primary particles, so the cycle performance and rate performance of the resulting battery are poor. The positive electrode material of Comparative Example 2 is formed of secondary particles, and the lithium ion migration speed is slightly improved. However, since there is no coating layer, the electrolyte retention ability of the particles is poor, the contact area between the positive electrode material and the electrolyte is limited, the lithium ion migration is disordered, the structural stability of the electrode material is poor, and the cycle performance and rate performance of the battery are poor. The coverage rate and coating thickness of the positive electrode material of Comparative Example 3 are too large, and the particle size ratio of the secondary particles to the primary particles is extremely low, so that the lithium ions are difficult to migrate, and the discharge speed of the battery is very poor.
[0110] As can be seen, the positive electrode material provided in the present disclosure can effectively improve the rate performance and cycle performance of the battery, and promote the use of the positive electrode material in the battery.
[0111] Although several embodiments of the present disclosure have been described above, they cannot be understood as limiting the scope of the present disclosure. However, some improvements and modifications may be made by those skilled in the art without departing from the principle of the present disclosure, and they shall be included in the protection scope of the present disclosure.
Claims
1. secondary particles formed by laminating a plurality of primary particles; a rock salt phase coating layer disposed on the surface of the secondary particles; Including, A positive electrode material, wherein a ratio of a particle size of the secondary particles to an average particle size of the plurality of primary particles is 1.5 or more, and the primary particles and the rock salt phase coating layer each contain a nickel-based active material.
2. The nickel-based active material has the chemical formula Li 1-a A b (Ni m M 1-m ) X x O 2 Z z 2. The cathode material of claim 1 , comprising a material of the formula: wherein -0.1≦a≦0.1; A comprises one or more of Na, K, Be, Mg, Ca, and B; 0≦b≦0.1; M comprises one or more of Mn, Co, and Al; 0<m≦1; X comprises one or more of Zr, V, Ti, Cr, Fe, Co, Ni, Zn, Nb, Mo, Os, W, and Y; 0≦x≦0.1; Z comprises one or more of F, Cl, Br, and I; and 0≦z≦0.
1.
3. 2. The positive electrode material according to claim 1, wherein a coverage of the rock salt phase coating layer on the surface of the secondary particles is in the range of 10% to 90%.
4. When the coverage is 20% or less, a ratio r of the particle size of the secondary particles to the average particle size of the primary particles satisfies 1.5≦r≦3; when the coverage is greater than 20% and not greater than 50%, a ratio r of the particle size of the secondary particles to the average particle size of the plurality of primary particles satisfies 3<r≦10; When the coverage is greater than 50% and not greater than 80%, a ratio r of the particle size of the secondary particle to the average particle size of the plurality of primary particles satisfies 10<r≦50; When the coverage is greater than 80%, a ratio r of the particle size of the secondary particles to the average particle size of the primary particles satisfies r>50. The positive electrode material according to claim 3 .
5. The positive electrode material according to any one of claims 1 to 4, wherein a coverage of the rock salt phase coating layer on the surface of the secondary particles is in the range of 50% to 80%.
6. 6. The cathode material according to claim 1, wherein the particle size of the secondary particles is 15 μm or less.
7. The positive electrode material according to any one of claims 1 to 6, wherein the rock salt phase coating layer has a thickness in the range of 1 nm to 20 nm.
8. The positive electrode material according to any one of claims 1 to 7, wherein the rock salt phase coating layer has a thickness in the range of 5 nm to 15 nm.
9. The positive electrode material according to any one of claims 1 to 8, wherein the secondary particles have a layered hexagonal close-packed structure and belong to the space group R3m; and in an X-ray diffraction pattern of the positive electrode material, a full width at half maximum of a diffraction peak of a (104) crystal plane of the positive electrode material is 0.1 to 0.
2.
10. The positive electrode material according to claim 9, wherein the full width at half maximum of the diffraction peak of the (104) crystal plane of the positive electrode material is 0.105 to 0.
130.
11. 11. The positive electrode material of claim 1, wherein the rock salt phase coating layer and the nickel-based active material each comprise a doped lithium nickel cobalt manganese oxide or an undoped lithium nickel cobalt manganese oxide.
12. The undoped lithium nickel cobalt manganese oxide is Li(Ni m Co n Mn 1-m-n ) O 2 12. The cathode material of claim 11 having a chemical formula of: where 0<m<1, 0<n<1, and 0<m+n<1.
13. 13. The cathode material of claim 11 or 12, wherein the doping elements of the doped lithium nickel cobalt manganese oxide include one or more of Na, K, Be, Mg, Ca, B, Zr, V, Ti, Cr, Y, Fe, Co, Ni, Zn, Nb, Mo, Os, W, F, Cl, Br, and I.
14. The doped lithium nickel cobalt manganese oxide or the undoped lithium nickel cobalt manganese oxide is Li 1-a A b (Ni m Co n Mn 1-m-n ) X x O 2 Z z 14. The cathode material of claim 11 having a chemical formula of: wherein -0.1≦a≦0.1, A comprises one or more of Na, K, Be, Mg, Ca, and B, 0≦b≦0.1, X comprises one or more of Zr, V, Ti, Cr, Fe, Co, Ni, Zn, Y, Nb, Mo, Os, and W, 0≦x≦0.1, and Z comprises one or more of F, Cl, Br, and I, and 0≦z≦0.
1.
15. A positive electrode sheet comprising a current collector and the positive electrode material according to claim 1 disposed on the current collector.
16. A positive electrode comprising the positive electrode sheet according to claim 15; Negative electrode and A secondary battery comprising:
17. 17. The secondary battery of claim 16, further comprising an electrolyte and a separator located between the positive electrode and the negative electrode.
18. 17. The secondary battery of claim 16, further comprising a solid or semi-solid electrolyte located between the positive electrode and the negative electrode.
19. A vehicle comprising the secondary battery according to any one of claims 16 to 18.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary battery
JP2021018897A
Positive electrode active material and lithium secondary battery comprising the same
JP2021158105A
Positive electrode active material for lithium ion secondary battery, manufacturing method of positive electrode active material for lithium ion secondary battery, lithium ion secondary battery
JP2022038350A
Method for preparing positive electrode active material for lithium secondary battery, and positive electrode active material prepared thereby
WO2021112596A1